1999
DOI: 10.1007/s11769-999-0019-y
|View full text |Cite
|
Sign up to set email alerts
|

Remote sensing based estimation system for winter wheat yield in North China Plain

Abstract: This paper presents the applications of Landsat Thematic Mapper (TM) data and Advanced Very High Resolution Radiometer (AVHRR) time series data for winter wheat production estimation in North China Plain. The key techniques are described systematically about winter wheat yield estimation system, including automatically extracting wheat area, simulating and monitoring wheat growth situation, building wheat unit yield model of large area and forecasting wheat production. Pattern recognition technique was applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Ammonium bicarbonate (NH 4 HCO 3 ) was mostly applied as the fertilizer. In the model, the crops were fertilized twice in the growing period, with 86 kg of pure nitrogen per hectare each time, and were irrigated four times, with 60 mm of water each time, during the periods of wintering (12/01), stem elongation (3/29), heading (4/20), and grain filling (5/15) [51,52]. Phosphorus and potassium were not simulated in the model.…”
Section: Data Inputs Calibration and Validation Of The Dssat Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Ammonium bicarbonate (NH 4 HCO 3 ) was mostly applied as the fertilizer. In the model, the crops were fertilized twice in the growing period, with 86 kg of pure nitrogen per hectare each time, and were irrigated four times, with 60 mm of water each time, during the periods of wintering (12/01), stem elongation (3/29), heading (4/20), and grain filling (5/15) [51,52]. Phosphorus and potassium were not simulated in the model.…”
Section: Data Inputs Calibration and Validation Of The Dssat Modelmentioning
confidence: 99%
“…In the DSSAT model, the infiltration and soil water dynamics were simulated based on the equation provided by the Soil Conservations Service of America (Washington, DC, USA) and the one-dimensional water balance model developed by Ritchie [57] (pp. [41][42][43][44][45][46][47][48][49][50][51][52][53][54]. The evapotranspiration was simulated daily using the Penman-Monteith method in FAO-56.…”
Section: Data Inputs Calibration and Validation Of The Dssat Modelmentioning
confidence: 99%
“…RMSE measures the average magnitude of the error, providing an absolute measure of fit, while NRMSE provides a normalized measure of these errors, allowing for their comparison across different datasets or variables. Liu et al [37] suggested that the simulated results are very good when the NRMSE is below or equal to 15%. If NRMSE is above 15% but below or equal to 30%, the simulation performance is considered good.…”
Section: Discussionmentioning
confidence: 99%
“…The Root Mean Square Error of homogenization NRMSE, and the consistency index D were used to quantify the validation accuracy. The specific calculation formula is as follows [46].…”
Section: Methodsmentioning
confidence: 99%